Language Policy:How do organisations ensure that instructive texts are written in a language that is understood by their end users? - Lauridsen, Karen M. (HERMES - Journal of Language and Communication in Business, 2008)
Like any other text, instructive texts function within a given cultural and situational setting and may only be available in one language. However, the end users may not be familiar with that language and therefore unable to read and understand the instructions. This article therefore argues that instructive texts should always be available in a language that is understood by the end users, and that a corporate communication policy which includes a language policy should ensure that this is in fact the case for all instructive texts.